Answer:
x = 1
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Step-by-step explanation:
<u>Step 1: Define Equation</u>
3(4x - 5) - 4x + 1 = -6
<u>Step 2: Solve for </u><em><u>x</u></em>
- Distribute 3: 12x - 15 - 4x + 1 = -6
- Combine like terms: 8x - 14 = -6
- Isolate <em>x</em> term: 8x = 8
- Isolate <em>x</em>: x = 1
<u>Step 3: Check</u>
<em>Plug in x into the original equation to verify it's a solution.</em>
- Substitute in <em>x</em>: 3(4(1) - 5) - 4(1) + 1 = -6
- Multiply: 3(4 - 5) - 4 + 1 = -6
- Subtract: 3(-1) - 4 + 1 = -6
- Multiply: -3 - 4 + 1 = -6
- Subtract: -7 + 1 = -6
- Add: -6 = -6
Here we see that -6 does indeed equal -6.
∴ x = 1 is the solution to the equation.
Answer:
Yes
Step-by-step explanation:
Yes, because each x has one specific y.
Answer:
X+4
Step-by-step explanation:
8+3x=25-x
3x+x=24-8
4x+16
Answer:
65
Step-by-step explanation: